2013
DOI: 10.1038/srep03373
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanin-dependent anoxygenic photosynthesis in coloured flower petals?

Abstract: Chlorophylless flower petals are known to be composed of non-photosynthetic tissues. Here, we show that the light energy storage that can be photoacoustically measured in flower petals of Petunia hybrida is approximately 10-12%. We found that the supposed chlorophylless photosynthesis is an anoxygenic, anthocyanin-dependent process occurring in blue flower petals (ADAPFP), accompanied by non-respiratory light-dependent oxygen uptake and a 1.5-fold photoinduced increase in ATP levels. Using a simple, adhesive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 30 publications
0
13
0
5
Order By: Relevance
“…Broennum-Hansen and Flink 380 reported that the anthocyanins containing the disaccharide sambubiose (a component of some glycosides), 380 are more stable than glucose containing monosaccharidic anthocyanins. Thus, the choice is not a simple task, because anthocyanin extracts are strongly affected by pH, 382 processing and storage temperature, 383 concentration, 384 aggregation of dyes, 385 solvents, 386 light intensity and frequency, 387 presence of oxygen, 388,389 metallic ions, 390,391 enzymes and other substances. 381 For the use of anthocyanins as dyes in DSSCs, the aforementioned structural variations are critical in the choice of the natural sensitizer characterized by the most favourable structural and optical properties (e.g., maximum absorptionl max , e, colour stability).…”
Section: Anthocyaninsmentioning
confidence: 99%
“…Broennum-Hansen and Flink 380 reported that the anthocyanins containing the disaccharide sambubiose (a component of some glycosides), 380 are more stable than glucose containing monosaccharidic anthocyanins. Thus, the choice is not a simple task, because anthocyanin extracts are strongly affected by pH, 382 processing and storage temperature, 383 concentration, 384 aggregation of dyes, 385 solvents, 386 light intensity and frequency, 387 presence of oxygen, 388,389 metallic ions, 390,391 enzymes and other substances. 381 For the use of anthocyanins as dyes in DSSCs, the aforementioned structural variations are critical in the choice of the natural sensitizer characterized by the most favourable structural and optical properties (e.g., maximum absorptionl max , e, colour stability).…”
Section: Anthocyaninsmentioning
confidence: 99%
“…Ме тод ін дук ції флуо рес цен ції хло ро фі лу (ФХ) є пер спек тив ним у мо ні то рин гу дов кіл ля, ос кільки вив чен ня кі не ти ки флуо рес цен ції може на да ти свід чен ня про ха рак тер ак тив ності зо внішньо го сере до ви ща і вплив його на па ра мет ри фо то син те зу. Цю ін фор ма цію мож на ви ко риста ти для еко ло гічно го мо ні то рин гу та оцін ки стій кості фо то син тезую чих ор га ніз мів (Lysenko et al, 2013).…”
Section: вступunclassified
“…ПОЛІЩУК, 2017 який вхо дить до скла ду ор га ніз му, знач но ниж ча ніж флуо рес цен ція роз чи ну хло ро фі лу від по відної кон цен тра ції. В по даль шо му ці спос те ре жен ня ста ли ос но вою в ро зу мін ні яви ща фо то хі міч но го га сін ня флуо рес цен ції, коли збу дже на мо ле ку ла, пе ре хо дя чи до ос нов но го, не збу дже но го, ста ну, від дає час ти ну сво єї енер гії для здій снен ня фо тосин те тич них про це сів (Lysenko et al, 2013).…”
Section: вступunclassified
“…In a similar vein, we did not observe any direct effects of floral tissue damage due to the robber hole or nectar removal on female plant reproduction. These effects may only be common in cases where (1) the robber damages floral parts that can photosynthesize (Lysenko & Varduny 2013) and that fixed carbon makes up an important component of the plant's total carbon budget (Galen, Dawson & Stanton 1993), (2) robbing damages sexual organs of the flowers while robbing (McDade & Kinsman 1980;Galen 1983), or (3) subsequent nectar production by robbed flowers exacts a fitness cost to the plant. Carbohydrate costs to producing nectar can be extreme in some cases (Southwick 1984;Pyke 1991;Ordano & Ornelas 2005); in these systems, repeated nectar removal by robbers may exact severe fitness consequences for the plant.…”
Section: I R E C T E F F E C T S O F N E C T a R R O B B I N Gmentioning
confidence: 99%